Conhecendo Herbert Caro - Neumann, Gerson R. (Contingentia, 2008)
Herbert Caro has been known for his translations and musical knowledge. This article focuses on his musical conception in his articles: “Romance de Capa sem Espada”, published in 1977, and the literary aspect in “A mãe brasileira de Thomas Mann” from 1976.